A novel aqueous Li+ (or Na+)/Br− hybrid-ion battery with super high areal capacity and energy density. Issue 21 (30th April 2019) - Wang, Huaiqing; Wang, Renhe; Song, Zihan; Zhang, Huamin; Zhang, Hongzhang; Wang, Yonggang; Li, Xianfeng
Abstract : A novel hybrid ion battery, involving an aqueous redox pair and a super high loading ion intercalation anode, is proposed. Abstract : With the explosive growth in intermittent renewable sources and the global drive toward decarbonizing the energy economy, reliable large-scale electrical energy storage technologies with high safety and low cost are urgently needed. Aqueous batteries hold the intrinsic advantages of nonflammability and low cost; the zinc//bromine flow battery and LiMn2 O4 //NaTi2 (PO4 )3 aqueous rechargeable ion battery are two representative systems with relatively high voltages (1.6 V to 1.8 V in common aqueous solutions). However, the long-term cycling stability of intercalation/de-intercalation type cathode materials is easily impaired by pH fluctuance, while the deposition/dissolution-type zinc anode suffers from zinc dendrites and uneven deposition issues. To avoid these two issues, we propose a novel bromine//NaTi2 (PO4 )3 hybrid ion battery, involving an aqueous redox pair (Br3 − /Br −, with high reactivity in a pH range from 0 to 9) and a high-loading ion intercalation anode (NaTi2 (PO4 )3, with low working voltage and little volume change). First, the high-performance NTP@C nanoparticles are synthesized by a modified sol–gel method. Then, the three-dimensional NTP@C anode with super high mass loading is designed by employing a porous and conductive carbon substrate. The crossover of bromine in aqueous catholyte is suppressed by an effective bromine complexing agent and the insufficient ion transport in a thick solid anode is conquered by a negative flowing electrolyte. As a result, the hybrid ion battery shows high areal energy density, high power density and promising cycling stability. The full cell can deliver a high energy density and power density of 12.8 mW h cm −2 (109 W h kg −1 based on NTP@C and reacted LiBr) and 29.4 mW cm −2 (250 W kg −1 based on NTP@C and reacted LiBr), respectively. Moreover, the power density can reach 106 mW cm −2 with energy density remaining at 7.95 mW h cm −2 (68 W h kg −1 based on NTP@C and reacted LiBr) at a super high current density of 100 mA cm −2 . An average capacity loss of 0.075% per cycle is obtained during a 200-cycle test, demonstrating the great feasibility of the new system. Therefore, this hybrid battery has great potential in large scale electrical energy storage.